MARKETING MANAGEMENT IN THE SYSTEM OF ENSURING INVESTMENT ACTIVITY OF TERRITORIAL COMMUNITIES' ENTERPRISES - BLAHUN, Ivan; GRYNEVYCH, Liudmyla; DYKHA, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the integration of marketing management into the investment activity strategies of territorial communities. It discusses the necessity of adopting marketing approaches to attract investments, optimize resource allocation, and enhance socio-economic development. The research outlines fundamental principles, strategies, and methods for positioning communities as competitive and attractive investment destinations. In recent years, a notable decline in public funding for community development projects has emerged. Communities face challenges in securing financial resources for infrastructure, employment generation, and sustainable development. This gap underscores the need for proactive measures to attract investments. The article emphasizes that branding and marketing strategies are essential for territorial communities to establish a competitive edge and gain investor confidence. Marketing management, therefore, becomes a cornerstone for addressing these challenges and leveraging opportunities. Despite substantial academic discourse on investment and marketing strategies, the article identifies a significant gap: the lack of a systematic methodology to integrate marketing tools into the investment frameworks of territorial communities. The primary objective is to define and justify marketing management components that can catalyze investment activities.Marketing management is conceptualized as a system for effectively managing the processes of attracting, distributing, and utilizing investment resources. This approach prioritizes creating a favorable investment climate through strategic planning, implementation, and evaluation.That marketing management is an indispensable element of investment strategies for territorial communities. It enables systematic approaches to resource optimization, boosts community visibility, and fosters investor trust. The recommended strategies not only ensure economic stability but also create a foundation for sustainable growth. By integrating marketing into their operations, communities can build lasting relationships with investors, enhance their competitive positioning, and improve the quality of life for residents. Future research should focus on refining these methodologies and exploring advanced digital tools to amplify their impact.
Keywords: marketing; investment; investment activity; enterprise; territorial community; marketing management; enterprises; omnichannel marketing